Money divers - (:unkn) unknown (Ethel H. Traphagen, 2008)
Photo of a man diving from a boat and two other men swimming in the water.
Trinidad, money divers
Colour: Black and White; Style: Portrait; Other: Bordered, Divided
Photo. F.W.
Keywords: Postcards; Swimmers--Trinidad and Tobago; Boats and boating--Trinidad and Tobago; Divers--Trinidad and Tobago